Industrial training report: Perbadanan Perpustakaan Awam Selangor / Nursyazwani Mohamad Roslan - Mohamad Roslan, Nursyazwani (Faculty of Information Management, 2023)
Industrial training (IMC690) is a required course for all Bachelor of Information Science (Hons.) Library Management students before completing their studies. It is one of the obstacles students must overcome before receiving a bachelor's degree credential. Students are exposed to the real world of industry through industrial training, which enables them to think freely and aggressively in order to stand out. Furthermore, industrial training helps students better understand the breadth of work in the subject of librarianship. The purpose of this report is to detail the tasks and activities completed during the five months spent working with the PPAS. Organizational Background, Organizational Information, Industrial Training Activities, and Industrial Training Reflection are the four (4) chapters that make up this report. Personal ideas and opinions, lessons learned, limitations and recommendations were also incorporated in the application of knowledge, abilities, and experience in completing the work (knowledge gain).